Música na formação dos alunos do Instituto de Educação Ivoti : um século de história - Feldens, Irving (2008)
This is an analysis of the proposal of Musical Education offered by the Ivoti Educational Institute (Instituto de Educação Ivoti IEI) throughout its history. It points out the relevance and contribution of the teaching of music in the framework of the school s educational rationale. It starts by discussing in a transversal manner concepts that function as theoretical guidelines for the research project: curriculum, holistic training, the value of musical education for human beings and musical education in the school curriculum in the framework of a holistic training. Beginning in the second chapter, it analyses, on the basis of the IEI s historical and present records, the place and importance ascribed to music, both as a regular course and as an optional activity, at the various stages of the school s history in the towns of Taquari, Santa Cruz, São Leopoldo and presently in Ivoti. The dissertation describes the disciplines taught in the area of music, their contents and goals. It names the teachers who were in charge of the classes, the artistic results that were shown in performances, concerts and artistic excursions carried out in the state of Rio Grande do Sul, in Brazil and in other countries. In the discussion of the school s rationale for the teaching of music and its evolution in the course of the school s history, it highlights interfaces that associate concrete facts pointed out in the historical records and the concepts introduced and developed in the beginning of the dissertation. The conclusion offers a summary of the course of musical education integrated with the IEI s pedagogical rationale throughout its history and the results from the documental mapping materialized in the organization and digitalization of documents on the topic. Thus it breaks ground for other research projects on the basis of the collected material.